2013
DOI: 10.1371/journal.pone.0080817
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Long Noncoding RNA AK139328 Attenuates Ischemia/Reperfusion Injury in Mouse Livers

Abstract: Recently, increasing evidences had suggested that long noncoding RNAs (LncRNAs) are involved in a wide range of physiological and pathophysiological processes. Here we determined the LncRNA expression profile using microarray technology in mouse livers after ischemia/reperfusion treatment. Seventy one LncRNAs were upregulated, and 27 LncRNAs were downregulated in ischemia/reperfusion-treated mouse livers. Eleven of the most significantly deregulated LncRNAs were further validated by quantitative PCR assays. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 49 publications
0
97
0
Order By: Relevance
“…Zhao et al demonstrated that lncRNA MALAT1 was involved in myocardial ischaemia‐reperfusion and down‐regulation of MALAT1 contributed to the reduction of cardiomyocyte apoptosis 8. LncRNA AK139328, which has been indicated by Chen et al to be involved in liver I/R injury, is a vital member of lncRNAs 9. However, the mechanism and role of lncRNA AK139328 in MIRI have not been completely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al demonstrated that lncRNA MALAT1 was involved in myocardial ischaemia‐reperfusion and down‐regulation of MALAT1 contributed to the reduction of cardiomyocyte apoptosis 8. LncRNA AK139328, which has been indicated by Chen et al to be involved in liver I/R injury, is a vital member of lncRNAs 9. However, the mechanism and role of lncRNA AK139328 in MIRI have not been completely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence shows that lncRNAs are critical regulators of genes involved in a variety of human diseases including AKI [64][65][66]. Recently, microarray assays and RNAsequencing (RNA-seq) methods have been used to evaluate lncRNA expression in animal models of I/R injury or in patients with AKI [64][65][66].…”
Section: Long Non-coding Rnas and Akimentioning
confidence: 99%
“…Recently, microarray assays and RNAsequencing (RNA-seq) methods have been used to evaluate lncRNA expression in animal models of I/R injury or in patients with AKI [64][65][66]. A few lncRNAs are differentially expressed in models of I/R injury in comparison to the control group expression [64][65][66].…”
Section: Long Non-coding Rnas and Akimentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al showed that lncRNA N1LR reduces neuronal apoptosis and enhances cell proliferation in cerebral IR by targeting Nck1 gene expression [16]. Chen et al demonstrated that silencing of AK139328 inhibits NF-κB and caspase-3 activity with activation of the Akt signaling pathway in hepatic IRI [17]. However, the biological effect of MALAT1 in testicular IRI has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%